Engaging Indigenous Community Towards a Talaandig Language Learning and Cultural Sustainability - Villaluz, RSCJ, PhD., Geraldine D.; Tagalog, EdD, ISRM, Rita May P.; Saway, Aduna L., Bai (ASEAN Journal of Community Engagement, 2023)
The decreased use of indigenous language among the young generation of an indigenous community in the Southern Philippines has introduced apprehension among cultural practitioners, the chief administrator, and the community of elders. With the articulated need to strengthen language learning and sustain the culture among the young Talaandig members of the tribe, the chief administrator has proposed a community engagement process for addressing this concern. This study explores the Talaandig language learning and cultural sustainability through the active involvement of an indigenous community of parents–teachers, leaders, and culture practitioners of the Talaandig tribe in Bukidnon, Philippines. Indigenous research methods and ethnographic approaches have resulted in an orthography of sight words and decodable texts culled from community group discussions, which serve as sources of reading materials for early readers of the School of Living Traditions. The findings illustrate the following points for the sustainability of language and culture: (a) the orthography drawn from decodable texts and sounds advances reading comprehension and interest; (b) indigenous knowledge derived through community engagement promotes the attainment of education for sustainable development; (c) outcomes gained from community-engaged research builds foundations for a sustained community and academe relationship; and (d) community book writing centered on indigenous culture promotes community integrity, education for the environment, and language sustainability. It is hoped that the findings could become a basis for strengthening the Talaandig language learning and cultural sustainability in the future, contributing to the literature on Education for Sustainable Development 2030.